Method for producing carbonyl group-containing compound

The method of thermal decomposition of organic compounds in a pyrolysis system with carbon dioxide consumption addresses the inefficiency of existing carbon dioxide utilization technologies by converting CO2 into carbonyl group-containing compounds, effectively reducing carbon dioxide levels.

JP2025068839APending Publication Date: 2025-04-30MICROWAVE CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023178874
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Existing methods for using carbon dioxide as an industrial raw material are insufficient in effectively reducing carbon dioxide concentrations, necessitating a new technology that consumes carbon dioxide by converting it into another substance.

Method used

A method involving the thermal decomposition of an organic compound in a pyrolysis system with a carbon dioxide source, where carbon dioxide is consumed and converted into a carbonyl group-containing compound, utilizing gaseous carbon dioxide and electromagnetic wave irradiation for heating.

Benefits of technology

This method effectively consumes carbon dioxide by converting it into valuable carbonyl group-containing compounds, providing a new approach to mitigate carbon dioxide levels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068839000001
    Figure 2025068839000001
  • Figure 2025068839000002
    Figure 2025068839000002
  • Figure 2025068839000003
    Figure 2025068839000003
Patent Text Reader

Abstract

To provide a novel technique for converting carbon dioxide into another substance through its consumption.SOLUTION: Conversion and consumption of carbon dioxide gas can be achieved by a carbon dioxide reaction method comprising a step of subjecting a material containing an organic compound to a pyrolysis system supplied with a carbon dioxide source, and converting the carbon dioxide into a carbonyl group-containing compound mixture through a pyrolysis reaction using the organic compound and gaseous carbon dioxide as raw materials.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a carbonyl group-containing compound. More specifically, the present invention relates to a method for producing a low molecular weight compound having an introduced carbonyl group by using carbon dioxide gas as a raw material during the thermal decomposition of an organic compound. [Background technology]

[0002] In recent years, the concentration of carbon dioxide in the atmosphere has risen, raising concerns about rapid global warming. As the rise in carbon dioxide concentration is largely due to the burning of fossil fuels, efforts are needed to reduce the use of fossil fuels. Attempts have been made to use atomic and natural (light, wind, wave, etc.) energy as alternative energy sources to fossil fuels, but the shift to these forms of energy is not easy, as atomic energy poses the problem of waste disposal, and natural energy poses the problems of capital investment and unstable energy supply. For this reason, the dependency on fossil fuels remains high in the primary energy mix in many developed countries.

[0003] In view of this global dependency on fossil fuels, there are examples of using carbon dioxide as an industrial raw material. For example, examples of using carbon dioxide as a chemical or industrial raw material include the production of urea, the raw material for conversion to methanol, the raw material for inorganic carbonates, the raw material for organic carbonates, and the production of polyurethane. Another example of using carbon dioxide as a food raw material is the production of carbonated drinks. However, effective reduction of carbon dioxide cannot be expected only from these uses. Therefore, Non-Patent Document 1 proposes an attempt to collect carbon dioxide from the atmosphere and capture and store it (CCS), but there are issues such as storage space, and there are still high hurdles to practical application. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Renewable and Sustainable Energy Reviews, (2014), 39, 426 Summary of the Invention [Problem to be solved by the invention]

[0005] Effective reduction of carbon dioxide cannot be expected only from the conventional methods of using carbon dioxide. Therefore, the present invention aims to provide a new technology that consumes carbon dioxide by converting it into another substance (hereinafter, also referred to as "conversion consumption" of carbon dioxide). [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that by contacting an organic compound with gaseous carbon dioxide during its thermal decomposition, a carbonyl group is introduced into the decomposition product of the organic compound, and thus the carbon dioxide is consumed and converted into a carbonyl compound. The present invention has been completed based on this finding and through further research.

[0007] That is, the present invention provides the following aspects. Item 1. A method for producing a carbonyl group-containing compound, comprising the steps of subjecting a material containing an organic compound to a pyrolysis system to which a carbon dioxide source is supplied, and consuming the carbon dioxide through a pyrolysis reaction using the organic compound and gaseous carbon dioxide as raw materials to obtain a carbonyl group-containing compound. Item 2. The method according to item 1, wherein the material containing an organic compound is a polymer material containing polyolefin. Item 3. The method according to Item 1 or 2, wherein the heating conditions for constructing the pyrolysis system are achieved by electromagnetic wave irradiation. Item 4. The method according to Item 3, wherein the electromagnetic waves are microwaves. Item 5. The method according to any one of Items 1 to 4, wherein the heating conditions for constructing the pyrolysis system are 200 to 1000° C. Item 6. The method according to any one of Items 1 to 5, wherein the carbon dioxide source contains gaseous carbon dioxide and is used as the raw material in the pyrolysis system. Item 7. The production method according to Item 6, wherein the gaseous carbon dioxide as the carbon dioxide source is supplied so as to occupy 30% by volume or more of the pyrolysis system atmosphere. Item 8. The production method according to any one of Items 1 to 7, wherein the carbon dioxide source includes a carbonate and / or a carbon dioxide absorbent, and the pyrolysis system thermally decomposes the carbonate to generate gaseous carbon dioxide as the raw material, and / or releases the gaseous carbon dioxide as the raw material from the carbon dioxide absorbent. Item 9. The method according to any one of Items 1 to 8, wherein the atmosphere of the pyrolysis system during the pyrolysis reaction and the carbon dioxide introduction reaction is normal pressure. Item 10. The method according to any one of Items 1 to 8, wherein the polymer material is a waste material. Item 11. The method according to any one of Items 1 to 10, wherein the polyolefin is polyethylene, polypropylene, and / or polystyrene. Item 12. The method according to any one of Items 1 to 11, wherein the polymer material further contains another polymer compound selected from the group consisting of polyesters, polyamides, and polysaccharides. Item 13. A carbonyl group-containing compound obtained by the production method according to any one of items 1 to 12. Effect of the Invention

[0008] According to the present invention, a new technology is provided for consuming carbon dioxide by converting it into another substance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The method for producing a carbonyl group-containing compound of the present invention is characterized by comprising the steps of subjecting an organic compound to a pyrolysis system to which a carbon dioxide source is supplied, and consuming the carbon dioxide through a pyrolysis reaction using the organic compound and gaseous carbon dioxide as raw materials to obtain a carbonyl group-containing compound mixture. The method for producing a carbonyl group-containing compound of the present invention will be described in detail below.

[0010] [1. Materials containing organic compounds] In the present invention, carbon dioxide is consumed by being fixed in the form of a carbonyl compound, and therefore an organic compound is used as a source to be fixed.

[0011] The organic compound is not particularly limited as long as it can be decomposed in a pyrolysis system, and includes polymers and oligomers. In addition, since the origin of the organic compound is not particularly limited, the organic compound may be a synthetic product or a natural product (including a processed product made from a natural product).

[0012] Synthetic materials include synthetic polymers (wherein the degree of polymerization of the plastic monomer is 100 or more) and synthetic oligomers (wherein the degree of polymerization of the plastic monomer is 2 or more and less than 100).

[0013] Specific examples of synthetic polymers include plastics such as polyolefins (PO), polyesters (PEs), and polyamides (PA). Polyolefins include, but are not limited to, polyethylene (PE), polypropylene (PP), and polystyrene (PS). Polyesters include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN), etc. Polyamides include nylon 6 (Ny6), nylon 66 (Ny66), and aramid, etc.

[0014] The synthetic oligomers include partial decomposition products of the above synthetic polymers and materials of the above synthetic polymers.

[0015] Natural products include polysaccharides (having 20 or more repeating monosaccharide units) and oligosaccharides (having 2 or more but less than 20 repeating monosaccharide units).

[0016] Examples of polysaccharides include cellulose and starch, etc. Examples of oligosaccharides include partial hydrolysis products of the polysaccharides.

[0017] In one embodiment of the present invention, one of these organic compounds may be used alone, or a combination of two or more of them may be used.

[0018] In a preferred embodiment of the present invention, the organic compound includes a polymer. When the organic compound includes a polymer in the present invention, a material including the organic compound is also particularly referred to as a polymer material.

[0019] A preferred embodiment of the polymer material is waste. The waste may be industrial waste discharged from a company or general waste such as household garbage. The waste may be used or unused. Specific examples of waste include trim (end materials) generated during the manufacturing process of a product, off-spec products, recovered products distributed in the market, food waste, etc.

[0020] Therefore, among the constituents of polymer materials, more specific examples of plastics include pure plastics containing catalysts; plastic compounds (containing stabilizers such as ultraviolet absorbers and / or additives such as colorants); various molded plastic products (for example, automobile bumpers, door handles, wheel housings, wire harnesses, films, etc.); plastic bottles (including those with caps made of a different material than the bottle and / or labels made of a different material than the bottle affixed); synthetic fiber bundles (including those with surfaces treated with a binder); synthetic fiber clothing (fleece, shirts, jerseys, stockings, gloves, etc.), etc.

[0021] Furthermore, among the constituents of the polymer material, more specific examples of polysaccharides include cellulose fibers extracted from cotton, wood (a cellulose mixture containing cellulose, hemicellulose and lignin), powdered starch (derived from corn or potato), starch paste, paper (cardboard, photographic paper, etc.), and food waste (rice, potato, etc.).

[0022] The properties of the material containing an organic compound are not particularly limited because they are determined according to the molecular weight and type of the organic compound and the material composition, and examples thereof include liquid, semi-solid (paste-like, etc.), and solid. It is preferable to use a solid polymer material in a crushed or cut form so that the specific surface area is large. Specific examples of the crushed or cut form include granular forms with a maximum diameter of 20 mm or less, preferably 10 mm or less, more preferably 5 mm or less, and even more preferably 3 mm or less when the original form of the polymer material is a block; flake forms with a maximum diameter of 20 mm or less, preferably 10 mm or less, more preferably 5 mm or less, and even more preferably 3 mm or less when the original form of the polymer material is a film; and flake forms with a fiber length of 10 mm or less, preferably 3 mm or less, preferably in a state of being loosened into single fibers when the original form of the polymer material is fibrous. When the polymer material contains food materials containing moisture (e.g., rice, potatoes, etc.), it is preferable to prepare the food materials in a paste form.

[0023] When the polymer material is made by assembling a plurality of plastics, the plurality of plastics may be integrated once and then prepared into the above-mentioned form. The integration method is not particularly limited, and may be a method of subjecting the plastics to heating conditions that fluidize the plastics without thermal decomposition, and examples of the heating method include heating with a heat source and heating with infrared rays, and the temperature or output may be appropriately set by a person skilled in the art so as to fluidize the plastics without thermal decomposition.

[0024] The polymer material may also be deteriorated by exposure to ultraviolet light.

[0025] [2. Carbon dioxide source] In the present invention, a carbon dioxide source is used as a raw material for producing a carbonyl group-containing compound.

[0026] The carbon dioxide source may be gaseous carbon dioxide or a material that generates gaseous carbon dioxide in a pyrolysis system described below. Either gaseous carbon dioxide or the above-mentioned material may be used as the carbon dioxide source, or both may be used in combination.

[0027] Materials that generate gaseous carbon dioxide in a pyrolysis system include carbonates and carbon dioxide absorbents. Either the carbonates or the carbon dioxide absorbents may be used, or both may be used in combination.

[0028] Examples of carbonates include alkali metal carbonates (sodium carbonate, potassium carbonate, etc.), alkaline earth metal carbonates (calcium carbonate, etc.), zinc carbonate, magnesium carbonate, and ammonium carbonate; alkali metal bicarbonates (sodium bicarbonate, potassium bicarbonate, etc.), alkaline earth metal bicarbonates (calcium bicarbonate, etc.), zinc bicarbonate, magnesium bicarbonate, and ammonium bicarbonate. These carbonates may be used alone or in combination.

[0029] Examples of the carbon dioxide absorbent include amines that have absorbed carbon dioxide. Examples of the amines include alkylamines (e.g., methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dipentylamine, dihexylamine, methylethylamine, methylpropylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, etc.) and alkanolamines (e.g., methanolamine, ethanolamine, dimethanolamine, diethanolamine, dipropanolamine, trimethanolamine, triethanolamine, tripropanolamine, tributanolamine, trihexanolamine, etc.). These carbon dioxide absorbents may be used alone or in combination. In addition, the method of absorbing carbon dioxide into these carbon dioxide absorbents can be appropriately selected by a person skilled in the art from known amine scrubbing methods, etc.

[0030] The amount of the carbon dioxide source used relative to the material containing an organic compound is not particularly limited, and the stoichiometry of the carbonyl group introduction reaction for the thermal decomposition product of the organic compound can be selected arbitrarily.

[0031] When gaseous carbon dioxide is used as the carbon dioxide source, the carbon dioxide is supplied to the pyrolysis system so as to occupy, for example, 30% by volume or more, preferably 50% by volume or more, more preferably 80% by volume or more, even more preferably 90% by volume or more, and most preferably 100% by volume of the pyrolysis system atmosphere.

[0032] When a carbonate is used as a carbon dioxide source, the amount of the carbonate to be used is, for example, 0.05 parts by weight or more, preferably 0.08 parts by weight or more, more preferably 0.2 parts by weight or more, and even more preferably 0.4 parts by weight or more per part by weight of the material containing an organic compound. The upper limit of the amount of the carbonate to be used is not particularly limited, but may be, for example, 2 parts by weight or less, preferably 1 part by weight or less.

[0033] When a carbon dioxide absorbent is used as a carbon dioxide source, the amount of the carbon dioxide absorbent used is, for example, 0.05 parts by weight or more, preferably 0.08 parts by weight or more, more preferably 0.2 parts by weight or more, and even more preferably 0.4 parts by weight or more per part by weight of the material containing an organic compound. The upper limit of the amount of the carbon dioxide absorbent used is not particularly limited, but may be, for example, 2 parts by weight or less, preferably 1 part by weight or less.

[0034] [3. Pyrolysis system] A material containing an organic compound is subjected to a pyrolysis system to which a carbon dioxide source is supplied. Supplying a carbon dioxide source means that the carbon dioxide source is supplied from the outside and charged into the system, and when the carbon dioxide source is gaseous carbon dioxide, it means that the carbon dioxide source is charged so that the atmosphere in the pyrolysis system contains carbon dioxide at a concentration that exceeds the concentration originally contained in air, and when the carbon dioxide source is a carbonate and / or a carbon dioxide absorbent, it means that the carbonate and / or the carbon dioxide absorbent is simply charged into the pyrolysis system.

[0035] The pyrolysis system is constructed by including at least a material containing an organic compound and a carbon dioxide source, and by providing heating conditions. In the pyrolysis system, a pyrolysis reaction and a carbonyl group introduction reaction are carried out using a material containing an organic compound and gaseous carbon dioxide as raw materials. More specifically, an organic compound is gasified by a pyrolysis reaction, and the generated gas contains radicals, so that a carbonyl group is introduced into the gas molecule (carbon dioxide is converted and consumed) by reacting with carbon dioxide and / or carbon monoxide generated from carbon dioxide. In addition, depending on the type of microwave absorber described below (specifically, when the microwave absorber is silicon carbide, pitch coke, etc.), carbon monoxide is generated by reacting with a part of the microwave absorber and carbon dioxide, so that a carbonyl group is introduced into the gas molecule (carbon dioxide is converted and consumed) by reacting with the gas generated by the pyrolysis reaction of the organic compound. As a result, carbon dioxide is consumed and a carbonyl group-containing compound mixture is obtained. In the present invention, since such a pyrolysis system is adopted, it is possible to convert and consume carbon dioxide without using a catalyst.

[0036] [3-1. Heating means] The heating conditions are preferably provided by irradiation with electromagnetic waves. Examples of electromagnetic waves include sunlight, ultraviolet rays, infrared rays, and microwaves, and microwaves are particularly preferred from the viewpoint of improving the efficiency of pyrolysis of a material containing an organic compound into a gas containing radicals, and thus the efficiency of synthesis of a carbonyl group-containing compound.

[0037] The frequency of the microwave is not particularly limited, and may be, for example, 300 MHz to 300 GHz, preferably 900 MHz to 6 GHz, and more preferably 1 to 3 GHz. The microwave may be an electromagnetic wave having a wavelength of 1 mm to 1 m. The output (intensity) of the microwave is not particularly limited, and may be appropriately selected by a person skilled in the art according to the scale of the pyrolysis system, specifically, the amount of the material containing the organic compound to be irradiated with the microwave and the size of the reactor, and more preferably, according to the temperature conditions described below.

[0038] Microwave irradiation may be performed continuously or intermittently by repeating irradiation and pauses.

[0039] [3-2. Microwave absorbing materials] When microwaves are used as a heating means, it is preferable to further include a microwave absorbing material in the pyrolysis system. The microwave absorbing material is not particularly limited, and examples thereof include metals, metal salts, metal oxides (e.g., iron oxide, aluminum oxide, and a mixture of iron oxide and aluminum oxide, such as FeAlO 3 , aluminosilicates (including aluminosilicate minerals such as mullite, which is a mineral formed by artificially heating aluminosilicates at high temperatures), metal hydroxides, carbon (for example, graphite such as expanded graphite, activated carbon, carbon fiber, carbon nanotubes, carbon black, etc.), silicon carbide, pitch coke, etc. These microwave absorbing materials may be used alone or in combination of two or more types. Among these microwave absorbing materials, graphite (more preferably expanded graphite), carbon fiber, silicon carbide, metal oxides (more preferably FeAlO3 , aluminosilicates).

[0040] The mode in which the microwave absorbing material is included in the pyrolysis system is not particularly limited, but it may be present in the vicinity of the surface of the material containing an organic compound or on the surface of the material containing an organic compound. In other words, since the microwave absorbing material does not need to be uniformly attached to the surface of the material containing an organic compound, it may be mixed with the material containing an organic compound or not, and simply may be added from above the material containing an organic compound.

[0041] The shape of the microwave absorbing material is not particularly limited, and examples thereof include plate-like, block-like, granular, fibrous, etc. Regarding the plate-like or block-like microwave absorbing material, if it has a size that can be handled in the device, it can be used as it is without being crushed, or it can be crushed into particles and used.

[0042] The size of the microwave absorbing material may be, for particulates, an average particle diameter of 0.05 to 900 μm, preferably 0.1 to 0.5 μm, and for fibrous materials, an average fiber length of 5 mm or less, preferably 3 mm or less, more preferably 2.5 mm or less. The average particle diameter and average fiber length are values ​​measured by the method shown in item [3] of the Examples.

[0043] The amount of the microwave absorber used is not particularly limited, but from the viewpoint of further improving the heating efficiency by microwaves, the amount relative to 1 part by weight of the material containing an organic compound is preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, even more preferably 0.05 parts by weight or more, 0.055 parts by weight or more, 0.065 parts by weight or more, 0.075 parts by weight or more, 0.085 parts by weight or more, 0.095 parts by weight or more, or 0.1 parts by weight or more. In addition, from the viewpoint of avoiding a decrease in the thermal decomposition efficiency, the amount of the microwave absorber used relative to 1 part by weight of the material containing an organic compound is preferably 2 parts by weight or less, more preferably 1.1 parts by weight or less, even more preferably 0.6 parts by weight or less, 0.55 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less.

[0044] The following is a suitable example of the amount of microwave absorbing material to be used per part by weight of the material containing an organic compound. In the case of carbon or silicon carbide: preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, even more preferably 0.05 parts by weight or more, 0.055 parts by weight or more, 0.065 parts by weight or more, 0.075 parts by weight or more, 0.085 parts by weight or more, 0.095 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or more, and preferably 2 parts by weight or less, 1.1 parts by weight or less, 0.6 parts by weight or less, 0.55 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, 0.2 parts by weight, 0.15 parts by weight or less, or 0.1 parts by weight or less. FeAlO 3 In the case of (a), preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, even more preferably 0.4 parts by weight or more, and even more preferably 0.45 parts by weight or more. Preferably 2 parts by weight or less, 1.1 parts by weight or less, 0.6 parts by weight or less, or 0.55 parts by weight or less. In the case of aluminosilicate: preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, even more preferably 0.4 parts by weight or more, and even more preferably 0.45 parts by weight or more. Preferably 2 parts by weight or less, or 1.1 parts by weight or less.

[0045] [3-2. Temperature] The temperature in the pyrolysis system is not particularly limited as long as it is a temperature that allows at least the thermal decomposition of the organic compound. In addition, when a carbonate is used as the carbon dioxide source, the temperature in the pyrolysis system is selected to allow the thermal decomposition of the organic compound and the generation of gaseous carbon dioxide by the thermal decomposition of the carbonate. Furthermore, when a carbon dioxide absorbent is used as the carbon dioxide source, the temperature in the pyrolysis system is selected to allow the thermal decomposition of the organic compound and the release of gaseous carbon dioxide from the carbon dioxide absorbent. Specific examples of the temperature in the pyrolysis system include 200 to 1000°C, preferably 230 to 950°C, more preferably 290 to 900°C, even more preferably 340 to 850°C, even more preferably 390 to 800°C, and even more preferably 440 to 700°C. The time required from the start of heating to reach the above temperature may vary depending on the scale of the material containing the organic compound, but may be, for example, 5 to 60 minutes.

[0046] [3-3. Pressure] The pyrolysis system is typically a closed system. The pressure in the pyrolysis system is not particularly limited, and any of a reduced pressure state, normal pressure state, and pressurized state can be selected. Since the present invention is an excellent method for producing a carbonyl group-containing compound, the carbonyl group-containing compound can be effectively produced without pressurizing the pyrolysis system. From this viewpoint, a suitable example of the pressure in the pyrolysis system in the present invention is normal pressure or lower, and among these conditions, normal pressure is preferable from the viewpoint of efficiently producing a carbonyl group-containing compound. In this specification, "normal pressure" refers to a pressure within the range of normal pressure changes due to altitude and other environments based on standard atmospheric pressure (101.325 kPa), and refers to a pressure that is not actively subjected to pressure reduction or pressure increase.

[0047] [3-4.Operation] In the pyrolysis system, if a material containing an organic compound, gaseous carbon dioxide, and, if necessary, a microwave absorber are allowed to coexist under heating conditions, the pyrolysis reaction of the organic compound and the carbonyl group introduction reaction proceed. Therefore, no special operations are required during the reaction in the pyrolysis system.

[0048] For example, although a stirring operation is not required, appropriate stirring is permitted depending on the scale of the organic compound-containing material.

[0049] Furthermore, the reaction in the pyrolysis system is terminated when all of the organic compounds initially charged have been pyrolyzed and / or when a predetermined part or all of the carbon dioxide derived from the initially charged carbon dioxide source has been consumed, and the resulting carbonyl group-containing compound mixture can be recovered.

[0050] On the other hand, during the reaction in the pyrolysis system, or after a part or all of the organic compound initially charged has been pyrolyzed, and / or after a part or all of the carbon dioxide derived from the initially charged carbon dioxide source has been consumed, a material containing an organic compound and / or a carbon dioxide source can be newly and additionally charged into the pyrolysis system. Such additional charging can be carried out once or multiple times. In this case, the reaction in the pyrolysis system ends when all of the additionally charged organic compound has been pyrolyzed and / or when all of the carbon dioxide derived from the additionally charged carbon dioxide source has been consumed, and the resulting carbonyl group-containing compound mixture can be recovered.

[0051] The reaction in the pyrolysis system can be terminated by stopping heating and cooling the system so that the temperature in the system falls below the above heating conditions. The obtained carbonyl group-containing compound mixture can be recovered by cooling. The carbonyl group-containing compound mixture obtained by the present invention can be used as a new material, either as a mixture or as individual compounds contained in the mixture. In other words, according to the present invention, the carbonyl group-containing compound mixture produced by the consumption of carbon dioxide can be converted into a useful material as it is or by appropriately separating it. EXAMPLES

[0052] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the following examples and comparative examples, "parts" refers to proportions expressed by weight (parts by weight).

[0053] [Various measurement methods] [1] Method for measuring the amount of carbon dioxide converted and consumed in the product mixture The amount of carbon dioxide in the raw material mixture before the start of the reaction and the amount of carbon dioxide in the product mixture after the completion of the reaction were quantitatively measured using gas chromatography-mass spectrometry (GC-MS). The change in the amount of carbon dioxide before and after the reaction (on a molar basis) was taken as the amount of carbon dioxide fixed in the product mixture, and the proportion of the amount of carbon dioxide converted and consumed, relative to the amount of carbon dioxide initially supplied being taken as 100%, was derived as the carbon dioxide conversion consumption rate (%).

[0054] [2] Method for identifying the product compound The compounds generated by the reaction were subjected to qualitative and / or quantitative analysis using the above-mentioned GC-MS and infrared spectroscopy. In the infrared analysis, a test liquid prepared by absorbing the evolved gas in a solvent such as chloroform, a liquid obtained by cooling and liquefying the evolved gas, or a solid sample obtained by collecting the fine solid generated was subjected to infrared analysis.

[0055] [3] Measurement of average fiber length and average particle size Fiber length measurements were taken by visual gauge measurement (for fiber lengths 1 mm or greater) or length measurement using a stereo microscope at 50x magnification (for fiber lengths less than 1 mm). The average fiber length was taken as the arithmetic mean of the fiber length measurements taken for 20 randomly selected fibers. Particle size measurements were taken by visual gauge measurement (for particle sizes 1 mm or greater), length measurement using a stereo microscope at 50x magnification (for particle sizes less than 1 mm), or scanning electron microscopy (for measurements difficult using a stereo microscope). The mean particle size was determined as the arithmetic mean of the particle size measurements taken for 20 randomly selected particles.

[0056] [4] Temperature measurement The temperature of the reaction zone was measured using an infrared thermography camera or a thermocouple.

[0057] [5] Pressure measurement In order to grasp the amount (molar amount) of gas generated by the reaction, a pressure gauge was attached to the reactor to measure the pressure inside the reactor.

[0058] [Example 1] 5.02 parts of cement powder was placed at the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. Each grain was an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm, a melt mass flow rate of 13 g / 10 min, and a density of 960 kg / m 3 1.66 parts of polyethylene was placed on top of the cement powder, and 0.15 parts of expanded graphite with an average particle size of 0.12 μm under a scanning electron microscope were placed on top. Visual inspection revealed that expanded black smoke was attached to the surface of some of the polyethylene particles. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to capture the generated gas. The temperature at this time was 25°C. Gas was collected from the top of the quartz tube and analyzed, revealing that the CO 2 The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 25 minutes. The microwave output was gradually increased from 10 W, and after 25 minutes it reached 80 W. The temperature was initially room temperature, but gradually rose, reaching 450°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. In addition, C 2 H 4 , C 2 H 6 , C 3 H 4 O 2A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 1, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0059] [Example 2] 5.02 parts of cement powder was placed at the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. Each grain was an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm, a melt mass flow rate of 13 g / 10 min, and a density of 960 kg / m 3 A polymer material was prepared by thoroughly mixing 0.83 parts of polyethylene and 0.84 parts of crushed material obtained by removing labels and caps after use and washing PET bottles with a major axis of 3 mm or less. This mixture was placed on top of the cement powder, and 0.17 parts of expanded graphite with an average particle size of 0.12 μm under a scanning electron microscope was placed on top. It was visually confirmed that expanded black smoke was attached to the surfaces of some of the polyethylene particles and the PET bottle pieces. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to collect the generated gas. The temperature at this time was 26°C. The gas at the top of the quartz tube was sampled and analyzed, and it was found that the CO 2 The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 35 minutes. The microwave output was gradually increased from 10 W, and after 35 minutes it reached 120 W. The temperature was initially room temperature, but gradually rose, reaching 550°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. In addition, C 2 H 4 , C 2 H6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 1, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0060] [Example 3] 2.0 parts of alumina fiber bundles were laid on the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. 0.55 parts of flakes made of polyethylene, which were collected after use and chopped into pieces with a long diameter of 3 mm or less, 0.55 parts of crushed material made of PET bottles, which had been washed with water after removing their labels and caps, crushed into pieces with a long diameter of 3 mm or less, and 0.55 parts of crushed material made of cardboard with a thickness of 2 mm including a space portion, crushed into pieces with a long diameter of 3 mm or less, were thoroughly mixed to prepare a polymer material. This mixture was placed on top of the alumina fiber bundles, and 0.20 parts of expanded graphite with an average particle diameter of 0.12 μm under a scanning electron microscope were placed on top. Visual observation revealed that expanded black smoke was attached to the surfaces of some of the polyethylene flakes, PET bottle pieces, and cardboard flakes. Furthermore, 1.0 part of alumina fiber bundles was placed on the topmost part. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to capture the generated gas. The temperature at this time was 25°C. The gas at the top of the quartz tube was sampled and analyzed, and it was found that the CO 2The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 35 minutes. The microwave output was gradually increased from 10 W, and after 30 minutes it was raised to 150 W. The temperature was initially room temperature, but gradually rose, reaching 650°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. In addition, C 2 H 4 , C 2 H 6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 1, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0061] [Example 4] 2.0 parts of alumina fiber bundles were laid on the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. 0.10 parts of thin pieces made of polypropylene, which were collected and chopped into pieces with a long diameter of 3 mm or less, and 0.7 parts of pulverized material made of polybutylene terephthalate wire harness ends, which were pulverized into pieces with a long diameter of 2 mm or less, were thoroughly mixed to prepare a polymer material. This mixture was placed on top of the alumina fiber bundles, and 0.20 parts of expanded graphite with an average particle diameter of 0.12 μm under a scanning electron microscope were placed on top. It was visually confirmed that expanded black smoke was attached to the surface of some of the polypropylene flakes and wire harness flakes. Then, the inside of the quartz tube was replaced with carbon dioxide gas, and a completely uninflated balloon for collecting the generated gas was attached to the top of the quartz tube. The temperature at this time was 25°C. When the gas at the top of the quartz tube was collected and analyzed, it was found that CO 2 The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 945 MHz microwaves were irradiated through the quartz tube for 20 minutes. The microwave output was gradually increased from 10 W, and after 20 minutes it was raised to 90 W. The temperature was initially room temperature, but gradually rose, reaching 350°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. Furthermore, C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 1, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0062] [Example 5] 3.0 parts of an alumina fiber bundle were placed at the bottom of a 300 ml round-bottom flask. Nylon 6 and polyethylene laminate film used to package food was collected, chopped into pieces with a long diameter of 3 mm or less, and lightly compressed with fingers to harden. 2.0 parts of a thin piece of polymer material was placed on top of the alumina fiber bundle. 0.18 parts of graphite with an average particle size of 0.25 μm under a scanning electron microscope were then placed on top. Visual inspection revealed that graphite was attached to part of the surface of the film. 1.0 part of powdered calcium carbonate was then placed on top of this. A completely uninflated balloon was then attached to the top of the round-bottom flask to collect the generated gas. Gas was collected from the top of the round-bottom flask and analyzed, revealing that the carbon dioxide gas was 100% CO. 2 The amount of the saturation was less than 1%. The round-bottom flask with the uninflated balloon was placed in a microwave irradiation device (product name: μE X) manufactured by Shikoku Keisokuki Kogyo Co., Ltd., and 2.45 GHz microwaves were irradiated through the round-bottom flask for 60 minutes. The microwave output was gradually increased from 10 W, and after 60 minutes it was increased to 500 W. The temperature was initially room temperature, but gradually increased and reached 480°C. The temperature was measured using a thermocouple installed 10 mm above the surface of the solid matter in the round-bottom flask. As the temperature increased, gaseous matter was generated in the round-bottom flask and accumulated in the balloon. Gas was generated during the reaction, which was thought to be due to the rapid decomposition of calcium carbonate. Carbon dioxide was likely generated. The pressure during the reaction was always normal pressure. When a portion of the gas in the top of the round-bottom flask and in the balloon was collected and analyzed, no carbon dioxide was detected. When dilute sulfuric acid was dropped into the residue in the round-bottom flask, no gas was generated, and the 1.0 part of calcium carbonate added initially was completely decomposed. Also, the gas in the round-bottom flask and the balloon emits C 2 H 4 , C 2 H 6 , C 3 H 4 O 2A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 1, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0063] [Example 6] 3.0 parts of alumina fiber bundles were placed at the bottom of a 300 ml round-bottom flask. 10 parts of waste automobile gasoline tanks made of polyethylene and nylon 66, and 10 parts of waste automobile bumpers made of polypropylene were simultaneously shredded to prepare a polymer material. The shredder dust constituting this polymer material had a major axis of 3 mm or less. 3.0 parts of the shredder dust were placed on top of the alumina fiber bundles. In addition, 0.18 parts of carbon fiber, which had been untangled to a single fiber with the length of the carbon fiber bundles adjusted to 2 mm or less, were placed on top. Visual inspection showed that the shredder dust was dark in color. 0.5 parts of powdered magnesium carbonate were placed on top of it. A completely uninflated balloon was then attached to the top of the round-bottom flask to collect the generated gas. When the gas at the top of the round-bottom flask was collected and analyzed, the CO2 was less than 1%. This is thought to be a measurement of the remaining air at the top of the flask. The round-bottom flask with the uninflated balloon was placed in a microwave irradiation device (product name: μE X) manufactured by Shikoku Keisokuki Kogyo Co., Ltd., and 2.45 GHz microwaves were irradiated through the round-bottom flask for 60 minutes. The microwave output was gradually increased from 10 W, and after 30 minutes it was increased to 300 W. The temperature was initially room temperature, but gradually increased and reached 300°C. The temperature was measured using a thermocouple installed 10 mm above the surface of the solid matter in the round-bottom flask. As the temperature increased, gaseous matter was generated in the round-bottom flask and accumulated in the balloon. Gas was generated during the reaction, which was thought to be due to the rapid decomposition of magnesium carbonate. Carbon dioxide was likely generated. The pressure during the reaction was always normal pressure. When a portion of the gas in the top of the flask and in the balloon was collected and analyzed, 10% carbon dioxide was detected. Carefully, 3.0 parts of the shredder dust and 0.15 parts of graphite (not expanded graphite) were added to the round-bottom flask so that gas such as air did not enter the flask. It was confirmed that the volume of the balloon connected to the top of the round-bottom flask did not change before and after this. The microwave power was again gradually increased from 10 W, and after 30 minutes it was increased to 5000 W. The temperature was initially 50°C, but rose rapidly, reaching 650°C. The balloon connected to the top of the round-bottom flask expanded further. Some of the gas from the top of the flask and inside the balloon was sampled and analyzed, and no carbon dioxide was detected.When dilute sulfuric acid was added dropwise to the residue in the round-bottom flask, no gas was generated, and the 0.5 parts of magnesium carbonate added initially had completely decomposed. In addition, gas was observed from the top of the round-bottom flask and in the balloon. 2 H 4 , C 2 H 6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 1, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0064] [Example 7] 3.0 parts of alumina fiber bundles were placed at the bottom of a 300 ml round-bottom flask. 1.0 part of a used polyethylene plastic glove, 0.8 parts of a 0.3 μm-thick biaxially oriented polyethylene naphthalate film were collected, cut into pieces with a long diameter of 2 mm or less, and mixed well to prepare a polymer material consisting of 1.0 part of a thin piece, and 0.7 parts of a commercially available heat-resistant glove made of aramid fiber, which was cut off only from the finger parts before being discarded after use, and placed on the alumina fiber bundle. In addition, 1.0 part of commercially available silicon carbide with an average particle size of 0.8 mm measured under a stereomicroscope was placed on it. Visual observation showed that silicon carbide particles were attached to part of the surface of the polymer material. The top of the round-bottom flask was replaced with carbon dioxide gas, and a completely uninflated balloon was attached. The temperature at this time was 25°C. The gas collected from the top of the flask was CO 2The yield was 100%. The round-bottom flask with the uninflated balloon was placed in a microwave irradiation device (product name: μEX) manufactured by Shikoku Keisokuki Kogyo Co., Ltd., and 2.45 GHz microwaves were irradiated through the round-bottom flask for 60 minutes. The microwave output was gradually increased from 10 W, and after 30 minutes, it was suddenly increased to 500 W. The temperature was initially room temperature, but rose over time and reached 470°C. The temperature was measured using a thermocouple installed 10 mm above the surface of the solid matter in the round-bottom flask. As the temperature increased, gaseous matter was generated in the round-bottom flask and accumulated in the balloon. It is believed that carbon dioxide was generated. The pressure during the reaction was always normal pressure. When a portion of the gas from the top of the flask and in the balloon was collected and analyzed, no carbon dioxide was detected. In addition, C 2 H 4 , C 2 H 6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 1, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0065] [Example 8] 5.02 parts of cement powder were laid on the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. A product was about to be disposed of, consisting of raw potatoes placed on a tray made of expanded polystyrene, and the tray was covered with a soft polyethylene film. The waste was crushed in a roll mill and mixed in a mixer until it became a paste, preparing a paste of a polymer material, and 3.0 parts of this paste were placed on top of the cement powder. Furthermore, 0.17 parts of expanded graphite with an average particle size of 0.12 μm under a scanning electron microscope were placed on top. It was visually confirmed that expanded black smoke was attached to part of the surface of the paste. Then, the inside of the quartz tube was replaced with carbon dioxide gas, and a completely uninflated balloon for collecting the generated gas was attached to the top of the quartz tube. The temperature at this time was 25°C. The gas at the top of the quartz tube was collected and analyzed, and it was found that the carbon dioxide gas was 0.01% CO 2 The reaction rate was 100%. The uninflated quartz tube with the balloon was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 50 minutes. The microwave output was gradually increased from 10 W, and after 35 minutes it was increased to 120 W. The temperature was initially room temperature, but gradually rose and reached 400°C. This temperature was measured from the outside of the quartz tube using an infrared thermography camera G100 manufactured by Nippon Avionics Co., Ltd. Gas began to be generated before the temperature reached 100°C, and as the temperature continued to rise, gaseous matter was generated in the quartz tube and accumulated in the balloon. The pressure during the reaction was always normal pressure. When a portion of the gas in the upper part of the quartz tube and in the balloon was collected and analyzed, no carbon dioxide was detected. When the residue in the quartz tube was removed, black matter that was thought to be cement powder, graphite, and potato carbide was found. C 2 H 4 , C 2 H 6 , C 3 H 4 O 2A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 1. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 1, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0066] [Example 9] The procedure was exactly the same as in Example 1, except that the gas replacing the inside of the quartz tube was changed to a mixed gas of 60 volumes of carbon dioxide and 40 volumes of nitrogen gas. After the reaction, no carbon dioxide was detected from the gas above the quartz tube or in the balloon. 2 H 4 , C 2 H 6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 2, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0067] [Example 10] The gas used to replace the inside of the quartz tube in Example 1 was changed to a mixed gas of 50 volumes of carbon dioxide and 50 volumes of air. Furthermore, the wavelength of the microwave used was changed from 2.45 GHz to 5.8 GHz, and the microwave output was gradually increased from 10 W, reaching 80 W after 20 minutes. The temperature was initially room temperature, but gradually increased, reaching 500°C. Other than these, the experiment was carried out in exactly the same manner as in Example 1. After the reaction, a portion of the gas in the upper part of the quartz tube and in the balloon was collected and analyzed, and no carbon dioxide was detected. In addition, C 2 H 4 , C 2 H 6 , C 3 H 4 O 2A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 2, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0068] [Example 11] The same procedure as in Example 1 was repeated except that 0.8 parts of a liquid compound in which carbon dioxide had been absorbed in ethylamine was added, the inside of the quartz tube was not replaced with carbon dioxide, and the contents of the quartz tube were gently stirred with a glass rod. After the reaction, a portion of the gas in the upper part of the quartz tube and in the balloon was sampled and analyzed. No carbon dioxide was detected, but ethylamine was detected. 2 H 4 , C 2 H 6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 2, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0069] [Example 12] Each grain is an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm. The melt mass flow rate is 13 g / 10 min and the density is 960 kg / m 310 parts of polyethylene were arranged on a glass plate. The top of the polyethylene was irradiated with ultraviolet light from a commercially available ultraviolet light generating lamp for 10 days to prepare a polymer material. A small amount of white powder was observed by visual inspection, but no gas was observed. The tentacles confirmed that the strength of the polyethylene particles had decreased. 5.02 parts of cement powder were placed at the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. 1.66 parts of polyethylene irradiated with ultraviolet light were placed on top of the cement powder, and 0.15 parts of expanded graphite with an average particle size of 0.12 μm under a scanning electron microscope were placed on top. Visual inspection confirmed that expanded black smoke was attached to the surface of some of the polyethylene particles. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to collect the generated gas. The temperature at this time was 25°C. Gas was collected from the top of the quartz tube and analyzed, and it was found that CO 2 The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 20 minutes. The microwave output was gradually increased from 10 W, and after 20 minutes it was raised to 60 W. The temperature was initially room temperature, but gradually rose, reaching 400°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. Furthermore, C 2 H 4 , C 2 H 6 , C 3 H 4 O 2 A carbonyl group-containing compound mixture was obtained that contained the above as a major compound and in which a carbonyl group was detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the major compounds shown in Table 2, there were also compounds in which a carbonyl group was detected by infrared analysis (carbonyl group-containing compounds).

[0070] [Example 13] Each grain is an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm. The melt mass flow rate is 13 g / 10 min and the density is 960 kg / m 3 A polymer material was prepared by thoroughly mixing 0.83 parts of polyethylene and 0.84 parts of crushed PET bottles, which had been washed with water after removing labels and caps, with a major axis of 3 mm or less. The mixture was arranged on a glass plate and irradiated with infrared light from a commercially available infrared generator for 10 hours. The mixture was integrated and no granular matter was observed. No gas was generated by visual inspection. The mass was crushed in a freeze crusher to a powder of 1 mm or less. 5.02 parts of cement powder were placed at the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. 0.7 parts of the frozen crushed powder were placed on top of the cement powder, and 0.17 parts of expanded graphite with an average particle diameter of 0.12 μm under a scanning electron microscope were placed on top. Visual inspection revealed that expanded black smoke was attached to the surfaces of some of the polyethylene particles and PET bottle pieces. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to capture the generated gas. The temperature at this time was 25°C. The gas at the top of the quartz tube was sampled and analyzed, and it was found that the CO 2 The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 25 minutes. The microwave output was gradually increased from 10 W, and after 25 minutes it reached 70 W. The temperature was initially room temperature, but gradually rose, reaching 450°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. In addition, C 2 H 4 , C 2 H 6 , C 3 H 4 O 2A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 2, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0071] [Example 14] 5.02 parts of cement powder was placed at the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm. Each grain was an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm, a melt mass flow rate of 13 g / 10 min, and a density of 960 kg / m 3 0.83 parts of polyethylene was placed on top of the cement powder, and FeAlO 3 0.42 parts of a mixture of iron oxide and aluminum oxide was placed on the surface of the polyethylene grain. 3 It was found that particles were attached. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to capture the generated gas. The temperature at this time was 26°C. The gas at the top of the quartz tube was sampled and analyzed, and it was found to be CO 2 The yield was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 15 minutes. The microwave output was gradually increased from 10 W, and after 15 minutes it reached 60 W. The temperature was initially room temperature, but then rose rapidly, reaching 550°C. This temperature was measured from the outside of the quartz tube using a G100 infrared thermography camera manufactured by Nippon Avionics Co., Ltd. As the temperature rose, gaseous matter was generated inside the quartz tube and accumulated inside the balloon. The pressure during the reaction was always normal pressure. When some of the gas from the top of the quartz tube and inside the balloon was collected and analyzed, no carbon dioxide was detected. Furthermore, C 2 H 4 , C 2 H 6 , C 3 H 4 O2 A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 2, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0072] [Example 15] At the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm, a single grain is placed in the shape of an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm. The melt mass flow rate is 13 g / 10 min and the density is 960 kg / m 3 A mixture of 0.18 parts of polyethylene and 0.002 parts of expanded graphite with an average particle size of 0.12 μm under a scanning electron microscope was placed in the tube. It was visually confirmed that expanded black smoke was attached to the surface of some of the polyethylene particles. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to capture the generated gas. The temperature at this time was 23°C. The gas at the top of the quartz tube was sampled and analyzed, and it was found that the CO 2 The reaction rate was 100%. The quartz tube with the uninflated balloon attached was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 80 minutes. The microwave output was gradually increased from 10 W, reaching 30 W after 30 minutes and 50 W after 50 minutes. The temperature was initially room temperature, but gradually increased to 240°C. This temperature was measured from the outside of the quartz tube using an infrared thermography camera G100 manufactured by Nippon Avionics Co., Ltd. The pressure during the reaction was always normal pressure. When a portion of the gas in the upper part of the quartz tube and in the balloon was collected and analyzed, carbon dioxide and a small amount of carbon monoxide were detected. In addition, C 2 H 4 , C 2 H 6 , C 3 H 6A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 2, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds).

[0073] [Example 16] At the bottom of a quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm, a single grain is placed in the shape of an elliptical cylinder with a major axis of 3 mm, a minor axis of 2 mm, and a length of 3 mm. The melt mass flow rate is 13 g / 10 min and the density is 960 kg / m 3 A mixture of 0.12 parts of polyethylene and 0.002 parts of expanded graphite with an average particle size of 0.12 μm under a scanning electron microscope was placed in the tube. It was visually confirmed that expanded black smoke was attached to the surface of some of the polyethylene particles. The inside of the quartz tube was then replaced with carbon dioxide gas, and a completely uninflated balloon was attached to the top of the quartz tube to capture the generated gas. The temperature at this time was 23°C. The gas at the top of the quartz tube was sampled and analyzed, and it was found to be CO 2 The reaction rate was 100%. The uninflated quartz tube with the balloon was placed in a microwave irradiation device manufactured by Fuji Electric Industries Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 60 minutes. The microwave output was gradually increased from 10 W, and after 25 minutes it was increased to 150 W. The temperature was initially room temperature, but gradually increased and reached 230°C. This temperature was measured from the outside of the quartz tube using an infrared thermography camera G100 manufactured by Nippon Avionics Co., Ltd. As the temperature increased, gaseous matter was generated in the quartz tube and accumulated in the balloon. The pressure during the reaction was always normal pressure. When a portion of the gas in the upper part of the quartz tube and in the balloon was collected and analyzed, carbon dioxide and a small amount of carbon monoxide were detected. In addition, a carbonyl group-containing compound mixture was obtained that contained carbon monoxide and the like as the main compound from the gas in the upper part of the quartz tube and in the balloon, and carbonyl groups were detected by infrared analysis of the quartz can deposits. The results are shown in Table 2.

[0074] [Example 17] The same procedure as in Example 15 was carried out, except that 0.09 parts of a plate-shaped aluminosilicate having a thickness of 1 mm and a longitudinal width of 7 mm was used instead of 0.002 parts of expanded black smoke having an average particle size of 0.12 μm. The aluminosilicate used contained 0.1 wt% sodium, and it was found by visual observation that polyethylene particles were attached to a part of the surface of the plate-shaped aluminosilicate before the start of the reaction. The microwave output was gradually increased from 10 W, and after 30 minutes it was increased to 70 W. The temperature was initially room temperature, but gradually increased and reached 220°C. The microwave was further increased to 90 W and 120 W, reaching 255°C after 80 minutes. The microwave output was adjusted to control the temperature to 255°C ± 5°C, and the reaction was carried out for 50 minutes. The pressure during the reaction was always normal pressure. In addition, C 2 H 4 , C 2 H 6 , C 3 H 6 A carbonyl group-containing compound mixture was obtained that contained the above as main compounds and in which carbonyl groups were detected by infrared analysis. The results are shown in Table 2. The carbonyl group-containing compound mixture contained a wide variety of compounds, and in addition to the main compounds shown in Table 2, there were also compounds in which carbonyl groups were detected by infrared analysis (carbonyl group-containing compounds). [Example 18] The same procedure as in Example 15 was carried out, except that 0.002 parts of expanded black smoke with an average particle size of 0.12 μm was replaced with 0.05 parts of mullite with an average particle size of 0.5 mm and 0.06 parts of plate-shaped mullite with a long width of 3 mm and a short width of 2 mm. It was visually confirmed that the polyethylene particles were mixed with the mullite particles before the reaction started. The microwave output was gradually increased from 10 W, and after 30 minutes it was increased to 50 W. The temperature was initially room temperature, but gradually increased and reached 200 ° C. The microwave was further increased to 70 W, 90 W, and 100 W every 10 minutes, and after 80 minutes it reached 230 ° C. The microwave output was adjusted to control the temperature between 230 ° C. and 235 ° C., and the reaction was carried out for 15 minutes. The temperature reached after 15 minutes was 235 ° C. A carbonyl group-containing compound mixture was obtained from the gas in the upper part of the quartz tube and the balloon, which contained carbon monoxide as a main compound and in which carbonyl groups were detected by infrared analysis of the quartz can deposit. The results are shown in Table 2.

[0075] [Comparative Example 1] The experiment was carried out in exactly the same manner as in Example 1, except that the inside of the quartz tube was not replaced with carbon dioxide gas but was kept as air. 2 H 4 , C 2 H 6 However, no carbonyl groups were detected in the product mixture. In other words, when carbon dioxide was not actively introduced and existed in the air at a dilute concentration of about 500 ppm, no carbon dioxide was observed to be incorporated into the pyrolysis mixture. The results are shown in Table 3.

[0076] [Comparative Example 2] A quartz tube with an inner diameter of 15 mm, an outer diameter of 18 mm, and a length of 1700 mm was filled with an equal volume mixture of ethylene gas and carbon dioxide at room temperature, and a completely uninflated balloon was attached to the top to collect the generated gas. This quartz tube was placed in a microwave irradiation device manufactured by Fuji Denpa Kogyo Co., Ltd., and 2.45 GHz microwaves were irradiated through the quartz tube for 25 minutes. An attempt was made to gradually increase the microwave output from 10 W, but most of it was reflected and it was not possible to increase the output. After 25 minutes, gas was collected from the quartz tube and analyzed, detecting only ethylene and carbon dioxide, confirming that no reaction had occurred.

[0077] [Comparative Example 3] The same operation as in Comparative Example 2 was carried out, except that 0.1 parts of expanded graphite were placed at the bottom of the quartz tube. The microwave output was gradually increased from 10 W, reaching 70 W after 25 minutes. The temperature was measured from the outside of the quartz tube with an infrared thermography camera G100 manufactured by Nippon Avionics Co., Ltd., and rose to 425°C. The pressure during the reaction did not increase and remained at normal pressure. The balloon at the top inflated slightly. When this gas was sampled and analyzed, ethylene, carbon dioxide, and carbon monoxide were detected, but no carbonyl compounds were detected. [Table 1]

[0078] [Table 2]

[0079] [Table 3]

Claims

1. A method for producing a carbonyl group-containing compound, comprising the steps of subjecting a material containing an organic compound to a pyrolysis system to which a carbon dioxide source is supplied, and consuming the carbon dioxide through a pyrolysis reaction using the organic compound and gaseous carbon dioxide as raw materials to obtain a carbonyl group-containing compound.

2. The method according to claim 1 , wherein the material containing an organic compound is a polymer material containing a polyolefin.

3. The method according to claim 1 , wherein the heating conditions for constructing the pyrolysis system are provided by electromagnetic wave irradiation.

4. The method according to claim 3 , wherein the electromagnetic waves are microwaves.

5. The method according to claim 1, wherein the heating condition for constructing the pyrolysis system is 200 to 1000°C.

6. The process of claim 1 , wherein the carbon dioxide source comprises gaseous carbon dioxide and is used as the feedstock in the pyrolysis system.

7. The method according to claim 6, wherein the gaseous carbon dioxide as the carbon dioxide source is supplied so as to occupy 30% by volume or more of the pyrolysis system atmosphere.

8. The production method according to claim 1, wherein the carbon dioxide source includes a carbonate and / or a carbon dioxide absorbent, and the pyrolysis system thermally decomposes the carbonate to generate gaseous carbon dioxide as the raw material, and / or releases the gaseous carbon dioxide as the raw material from the carbon dioxide absorbent.

9. The method according to claim 1 , wherein the atmosphere of the pyrolysis system during the pyrolysis reaction is atmospheric pressure.

10. The method of claim 1 , wherein the polymeric material is waste material.

11. The process according to claim 1 , wherein the polyolefin is polyethylene, polypropylene, and / or polystyrene.

12. The method of claim 1 , wherein the polymeric material further comprises another polymeric compound selected from the group consisting of polyesters, polyamides, and polysaccharides.

13. A carbonyl group-containing compound obtained by the method according to claim 1.